Reasoning with God reclaiming Shari'ah in the modern age - Abou El Fadl, Khaled 1963- (Rowman & Littlefield, 2014)
In Reasoning with God, renowned Islamic scholar Khaled Abou El Fadl explains not only what Shari'ah really means, but also the way it can revitalize and reengage contemporary Islam. After a prologue that provides an essential overview of Shari'ah, Abou El Fadl explores the moral trajectory of Islam in today's world. Weaving powerful personal stories with broader global examples, he shows the ways that some interpretations of Islam today have undermined its potential in peace and love. Rather than simply outlining challenges, however, the author provides constructive suggestions about how Muslims can reengage the ethical tradition of their faith through Shari'ah. As the world's second largest religion, Islam remains an important force on the global stage. Reasoning with God takes readers-both Muslim and non-Muslim-beyond superficial understandings of Shari'ah to a deeper understanding of its meaning and potential.